18s rDNA characterization and morphological investigation of the medicinal leech Hirudo medicinalis from Felaw Pond: 18s rDNA of Hirudo medicinalis - Jawdat Bilal, Samir (Cellular and Molecular Biology, 2024)
Hirudinea leeches are obligate parasites on a variety of vertebrates and have recently gained attention for their medicinal purposes. The present study aimed to improve the presence of Hirudo medicinalis in Kurdistan and Iraq (especially because it is regarded as a native species in this region). A total of 23 leech specimens were collected from Felaw Pond during January-July 2023. The collected specimens were investigated morphologically and their species were confirmed according to their partial sequence of 18s rDNA. Primers used were universal, C1 (ACCCGCTGAATTTAAGCAT) (forward primer), and C3 (CTCTTCAGAGTACTTTTCAAC) (reverse primer). The results of the morphological study and molecular sequencing of partial 18s rDNA demonstrated that all these leech specimens belonged to Hirudo medicinalis with an abundance of 0.13 leech/ m2. The present record was the first one investigating this species in Iraq.